Pendataan Demografi di Desa Lusiduawutun Kecamatan Nagawutung Kabupaten Lembata - Emilia F.M. Lizu; Erestiani Fahik; Petronela Mbas; Rosantiana G. Mbili; Matilda E.S.M. Yehuda Aron; Hendrikus L. Kaha (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
The program of Collection Of Demographic Data In Lusiduawutun Village, Nagawutung District, Lembata District Aims to strengthen the basic framework for efforts to realize inner and outer well-being, encouraging and motivating the potential of community human resources at KKN locations towards a dynamic life, having sufficient religious insight, a high and democratic work ethic. This research uses a qualitative approach with descriptive methods. Data collection was carried out through direct observation, interviews with related parties such as village heads, staff and the community as well as documentation regarding facilities and infrastructure as well as biographical data in Lusiduawutun village. The research results show that this program is very successful and can help in collecting biographical data for the Lusiduawutun village government.